Size Effect on Mechanical Behaviors of Intact Rocks Based on Enlarged Digital Models - Xiao, Huaiguang; He, Lei; Shi, Run; Song, Jiacheng; Tang, Yudi; Zhang, Qi; Shi, Peng (Frontiers in Earth Science, 2021)
The size effect on mechanical behaviors of rock materials has been a challenging topic. The previous research is mainly to study the relationship between known large-scale models and representative element volumes. However, only limited scale models can be obtained in situ or laboratory in many cases, so tests or simulations of mechanical response behaviors of large-scale models cannot be carried out. In order to obtain large-scale models, this paper proposes a multi-scale enlarged digital modeling method to synthesize granite models based on texture self-similarity. The representational ability of synthetic granite is analyzed by using mathematical statistics and finite-difference numerical method. The results show that synthetic granite can characterize the natural rock well in terms of texture morphology, geometric characteristics, and mechanical behaviors. Then, the size effect on mechanical behaviors of intact granite is performed based on an enlarged digital model. The results show that the uniaxial compressive strength of intact granite increases with the increase of model size. In addition, the relationship between heterogeneity and homogeneity is established at different unit scales by using the synthetic digital granite model. The enlarged digital rock model has great potential in studying size effects with rock heterogeneity.